Bilobalide inhibits 6-OHDA-induced activation of NF-κB and loss of dopaminergic neurons in rat substantia nigra - Li Ling-yun; Zhao Xi-lin; Fei Xi-feng; Gu Zhen-lun; Qin Zheng-hong; Liang Zhong-qin (Acta Pharmacologica Sinica, 2016)
Aim: To investigate the effects of bilobalide on the activation of NF-κB, and apoptosis of dopaminergic neurons induced by 6-hydroxydopamine (6-OHDA). Methods: A rat model of Parkinson's disease was produced with a unilateral infusion of 6-OHDA (8 μg) into the substantia nigra par compact. Bilobalide was administered 5, 10, and 20 mg/kg (ip) once a day for 7 d, starting 6 d prior to the 6-OHDA infusion. The rats were subjected to locomotor activity and rotational behavior testing 2 or 3 weeks after the 6-OHDA infusion. The expressions of tyrosine hydroxylase (TH) and NF-κB p65 were examined by immunofluorescence. The loss of dopaminergic neurons was detected by Nissl's staining. Terminal deoxynucleotidyl transferase-mediated dUTP nick-end labeling was used to identify apoptosis. Results: The behavioral changes due to 6-OHDA were significantly restored by bilobalide pretreatment. Bilobalide inhibited the 6-OHDA-induced loss of TH-positive neurons, decreased the activation of NF-κB, and protected dopaminergic neurons from apoptosis remarkably. Conclusion: NF-κB activation contributes to the 6-OHDA-induced loss of dopaminergic neurons, and the inhibition of the NF-κB pathway is likely to be involved in the neuroprotective effect of bilobalide.